2019
DOI: 10.1021/acs.inorgchem.9b02324
|View full text |Cite
|
Sign up to set email alerts
|

(Benz)Imidazolin-2-iminato Aluminum, Zinc, and Magnesium Complexes and Their Applications in Ring Opening Polymerization of ε-Caprolactone

Abstract: Synthesis and characterization of a new family of aluminum, magnesium, and zinc complexes supported by (benz)­imidazolin-2-iminato ligands are reported herein. Under different reaction conditions, (benz)­imidazolin-2-imine ligands reacted with metal alkyl precursors to afford the corresponding complexes, displaying mononuclear, binuclear, and trinuclear structures. Reaction in 1:1 stoichiometry at room temperature afforded the simple Lewis acid–base adducts, which exhibited distorted tetrahedral geometries aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…37,38 However, aluminium alkyl complexes with the imidiazoline-2-iminato ligand were only recently studied by the research groups of Inoue, 35,36 Masuda 39 and Eisen. 40 Recently, we developed an N-heterocyclic imine-based imino-phosphanamide ligand-supported yttrium complex [{NHI R P(Ph)N-Dipp}Y{NSiMe 3 } 2 ] (iPr, Me), where the ligand upon metalation is bonded with the yttrium ion in a monoanionic fashion similar to that of amidinate ligands. 41 The two donor nitrogen atoms attached to the phosphorus atom are completely different and it is interesting to note that this system is amenable to stereoelectronic modulation through substitution at the phosphorus and nitrogen centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 However, aluminium alkyl complexes with the imidiazoline-2-iminato ligand were only recently studied by the research groups of Inoue, 35,36 Masuda 39 and Eisen. 40 Recently, we developed an N-heterocyclic imine-based imino-phosphanamide ligand-supported yttrium complex [{NHI R P(Ph)N-Dipp}Y{NSiMe 3 } 2 ] (iPr, Me), where the ligand upon metalation is bonded with the yttrium ion in a monoanionic fashion similar to that of amidinate ligands. 41 The two donor nitrogen atoms attached to the phosphorus atom are completely different and it is interesting to note that this system is amenable to stereoelectronic modulation through substitution at the phosphorus and nitrogen centers.…”
Section: Introductionmentioning
confidence: 99%
“… 37,38 However, aluminium alkyl complexes with the imidiazoline-2-iminato ligand were only recently studied by the research groups of Inoue, 35,36 Masuda 39 and Eisen. 40 …”
Section: Introductionmentioning
confidence: 99%
“…These findings confirm that the polymerization proceeds via a coordination‐insertion mechanism. Furthermore, heating toluene solutions of 4 a and 4 b up to 80 °C for 6 h did not lead to cleavage of the P−H bond (Figures S37–S40), e.g., by methane (CH 4 ) elimination as observed for related imidazolin‐2‐imine‐aluminum complexes [50] . These observations indicate that the (NHC)PH ligands are not degraded and are therefore able to sustain a potential stereocontrol during the polymerization process.…”
Section: Methodsmentioning
confidence: 75%
“…Furthermore,h eating toluene solutionso f4a and 4b up to 80 8Cf or 6hdid not lead to cleavage of the PÀH bond (Figures S37-S40), e.g.,b ym ethane (CH 4 )e limination as observed for relatedi midazolin-2-imine-aluminum complexes. [50] These observations indicate that the (NHC)PH ligands are not degraded and are therefore able to sustain ap otential stereocontrol during the polymerization process. Accordingly, the high stereoselectivity achieved with catalysts 4a and 4b can have various reasons: In addition to conventional chainend control (CEC), in whicht he insertion of either LLA or DLA is controlled by the chirality of the previously enchained monomer,t he ligand might cooperativelyi nducee nantiomorphic site control (ESC), effecting the stereoselectivity of the catalysts ystem.…”
mentioning
confidence: 84%
“…Recently Zn(II) complexes bearing different Im R Nand analogous benzimidazolin-2-iminato ligands have been reported. [125][126] Scheme 26. appeared as a triplet at δH 1.58 and 1.26 ppm respectively. The molecular structure of 45 was confirmed by single-crystal X-ray diffraction analysis, which revealed that the geometry of central metal is distorted trigonal planar with the shortest Zn-N distance (1.974(2) Å) reported so far.…”
Section: Scheme 7 Copolymerization Of Ethylene/nbe Bymentioning
confidence: 99%